Predicting Digital Geotechnical Forensic Investigation using Internet of Things (IoT) - D, Sivakumar; E, Ravi (International Research Journal of Multidisciplinary Technovation, 2019)
Digital Forensic Investigations is explained as are sponse to an event that has already occurred in relation to information which is highly classified or is of prime importance to a criminal incident. Forensics Challenges in IoT Environments IoT would soon pervade all aspects of our life from managing our home temperature to thinking cars and smart management of the cities. The application of professional engineering principles and methodologies to investigating failures and incidents, usually to determine causation. Normally, it involves preparing a report of findings, which may form the basis for testimony in legal proceedings as an expert witness. A forensic engineer may serve as an engineering consultant to members of the legal profession and as an expert witness in courts of law, arbitration proceedings and administrative adjudication proceedings. Forensic engineering is a part of professional engineering practice that may cover all disciplines of engineering. It is a specialized set of skills that can include multidisciplinary training in failure analysis, simulation, safety, accelerated life testing and statistical analysis, as well as knowledge of the specific engineering field.